Putting Pain Assessment into Practice: Why Is It so Painful? - Linda S Franck; Elizabeth Bruce (Pain Research and Management)
OBJECTIVE: To explore some of the reasons for poor compliance with the use of standardized pain assessment tools in clinical practice, despite numerous guidelines and standards mandating their use.